Middle of nowhere [videorecording (DVD)] - Hardwick, Omari, 1974-; Corinealdi, Emayatzy, 1980-; Lawrence, Sharon, 1961-; Oyelowo, David (Lions Gate Entertainment, 2015)
Devoted wife Ruby drops out of medical school after her husband Derek receives an eight-year prison sentence, and struggles to find the courage to remain faithful and supportive as the demands of being a prison wife weigh heavily on her shoulders.